APPLICATION OF THE MFEP METHOD TO DETERMINE THE DISTRIBUTION OF SUBSIDED FERTILIZER ASSISTANCE TO THE FARMER GROUP OF PERUPUK VILLAGE, COAL REGENCY - Ayu Riski; William Ramdhan; Sumantri Sumantri (Informatika, Universitas Jenderal Soedirman, 2022)
The government through the Department of Food Crops, Horticulture and Food Security provides fertilizer subsidies to coal farmers, which annually reaches 15 tons of urea, SP 36 fertilizer, ZA fertilizer, NPK fertilizer, organic fertilizer. The fertilizer is used for rice, chili, onions, palm oil, eggplant and other types of agricultural crops that are cultivated in Batu Bara Regency by farmers. In the development of farmer groups in Batu Bara Regency, increasing years are increasing because Coal has become a granary, especially for rice which has greatly increased from 2018-2020 about an increase of 10% in the increase in the number of farmer groups. Problems that often occur at the Department of Food Crops, Horticulture and Food Security in Batu Bara Regency are related to determining the distribution of subsidized fertilizer assistance that is not right on target, to farmer groups who should deserve it but do not get it, because every year the number of farmers is increasing but the availability of fertilizer is limited. . Decision Support System (DSS) or Decision Support System (DSS) is a system that is able to provide problem solving and communication skills for problems with semi-structured and unstructured conditions. This system is used to help structure, where no one knows for sure how decisions should be made. This decision support system itself is intended to make decisions that are really feasible to get fertilizer assistance provided by the Indonesian government for the welfare of farmers and good results. obtained through the Distribution of Subsidized Fertilizer Aid.